Affective governmentality through gratitude: governmental rationality, education, and everyday life. Issue 4 (8th August 2022) - Shoshana, Avihu
ABSTRACT: One of the most thought-provoking contemporary developments in the study of governmentality is the concept of affective governmentality, alluding to how emotions play an important role in the regulation of individuals and populations. This article proposes to examine affective governmentality through the governmental construction and the phenomenological maintenance of gratitude among graduates of a state-run boarding school in Israel that serves disadvantaged students. For the current study, governmental and organizational documents were analyzed along with interviews with the school's administrators and graduates through several decades. My critical readings indicate that this boarding school has constructed its organizational identity through a relationship of gift and rescue . In-depth interviews with the boarding school's graduates reveal how they translated this governmental construction into accounts of gratitude. The article discusses the logic of gratitude as a 'role-taking emotion' which reinforces a specific emotional reflexivity and asymmetry in the relations between the State and its disadvantaged citizens.